Enjoying Every Moment: Improving Adolescent’s Subjective Well-Being Through Adolescent Mindfulness Program - Ardi Primasari; Kwartarini Wahyu Yuniarti (Faculty of Psychology, Universitas Gadjah Mada, 2021)
Adolescents often deal with pressures either from the internal or external environment that might trigger psychological issues related to behavior, emotion, academic achievement, and interpersonal relation. Specific intervention is particularly needed to improve adolescents’ subjective well-being in such situations. This research aimed at measuring the effectiveness of the Adolescent Mindfulness Program (Program Mindfulness Remaja, known as PRIMA) on adolescent subjective well-being. This research employed an experimental study with a switching replication design. Twenty-eight late adolescents aged 17-21 years-old previously identified with low or moderate subjective well-being participated in the study and received 9 sessions of the Mindfulness Program. Kentucky Inventory Mindfulness Scale (KIMS) was used to measure mindfulness and Satisfaction with Life Scale (SwSL) and Positive Affect & Negative Affect (PANAS) were used to measure subjective well-being. Results depicted significant improvement in adolescent subjective well-being (p= 0.000; p<0.001) after the intervention, with a therapeutic effect lasting for more or less than 2 weeks. The result of qualitative analysis indicated that self-compassion meditation was the most meaningful meditation for participants.